DE LA MILICIA A LA ARQUEOLOGÍA: PEDRO ARMILLAS Y SU CONTRIBUCIÓN ALA ARQUEOLOGÍA MEXICANA - Castaños, Carlos A.; Romero, Tonatiuh (CIENCIA ergo-sum; Vol. 6 Núm. 1 (1999): CIENCIA ergo-sum (marzo-junio 1999), 2017)
_